New hydroperoxybriarane diterpenoids from the octocoral Briareum violaceum. Issue 11 (15th March 2019) - Yao, Jia-Wen; Chi, Wei-Chiung; Xu, Jing-Hao; Lee, Gene-Hsiang; Chiang, Michael Y.; Peng, Bo-Rong; Lin, Nai-Cheng; Hu, Chiung-Chin; Fang, Lee-Shing; Li, Guo-Qiang; Chang, Yu-Chia; Hwang, Tsong-Long; et al.
Abstract: A known briarane, brianthein W (1 ), along with four new hydroperoxybriaranes, briaviolides R–U (2 –5 ), have been obtained from the octocoral Briareum violaceum . The absolute configuration of1 was determined by X-ray analysis for the first time and the structures of briaranes2 –5 were established by spectroscopic methods. Bioactivity study showed that briarane3 decreased the production of superoxide anions from human neutrophils. Graphical abstract: Image 1